THE DEVELOPMENT OF PSYCHOMETRIC INSTRUMENT-LOBG+BEHAVIORAL SCALE - Fatahyah, Yahya; wong, Kah Ong; Nor Mazlina, Ghazali; Nur Fatihah, Mat Yusoff; Azzahrah, Anuar; Merikan, Aren; Mohamad Azhari, Abu Bakar; Nor Hasniah, Ibrahim (PalArch Foundation, 2020)
The aim of this study is to develop LOBG+ Behavioral Scale as a valid instrument to measure behavior of an individual using variables named after animals. By associating the variables with common behavior of animals like fun-loving or hardworking, the association could be humorous and insightful to the individual. This provides a therapeutic and non-threatening environment for building rapport and enhances exploration in early stages of counselling process. A quantity research with a snowball sampling was carried out among 334 respondents in order to develop this instrument. The development was constructed based on the models; the Big Five Model, Sidek Color Personality and Leonard Personality index. Common items are relating to the main descriptors of Lion (Decisiveness), Otter (fun-loving), Beaver (Accuracy) and Golden Retriever (Agreeableness). These reviewed instruments are extracted from the literature review to form 40 items of the LOBG+ Behavioral Scale instrument. Content validation was performed by five expert panels indicated CVR of 0.95, indicating its high validity. SPSS analysis derives a Cronbach Alpha of 0.88 indicating its high reliability. The findings indicate that the LOBG+ Behavioural Scale can be used as a valid instrument to measure behavior.